Design and characterisation of a cell exposure system with high magnetic field homogeneity: RILZ coils - Rivera González, Marco-Xavier; López de Mingo, Isabel; Amuneke Ramírez, Alexandra; Maestú Unturbe, Ceferino (Frontiers in Bioengineering and Biotechnology, 2024)
In vitro studies requiring controlled exposure to low-frequency electromagnetic fields employ exposure systems with different geometries and configurations, the Helmholtz configuration being one of the most widely used. This configuration has limitations in the homogeneity of the spatial distribution of the magnetic field intensity values. We present the design, manufacturing, and characterisation of a new coil system, called RILZ configuration, which improves the distribution of magnetic field intensity values in the three dimensions of space for three different heights in comparison with the traditional circular coils in Helmholtz configuration. In addition, a comparative study of the cellular response in CT2A cultures exposed to an electromagnetic field of 50 Hz and 100 µT for 48 hours is performed with both exposure systems. The results of the study show reduced values of deviation from the central value of magnetic field intensity using the RILZ coil system. These differences are statistically significant compared to the Helmholtz configuration for the three Cartesian directions: x(p<0.01), y(p<0.01), z (p<0.01). In addition, the intensity values for three different heights are statistically significantly correlated using the RILZ coil system (p<0.01). The differences in cell behaviour are also statistically significant between the two systems (p<0.01) and may be directly related to the differences found in the distribution of intensity values between the two systems. This study highlights the importance of the homogeneity of the magnetic field intensity generated by the exposure systems used and offers an effective solution to control the magnetic field exposure parameters in in vitro assays.